A Co-NC catalyst for the catalytic conversion of 5-hydroxymethylfurfural and its preparation method

By using a Co-N-C catalyst, which consists of a three-dimensional multi-level Co nanostructure anchored on a nitrogen-doped carbon material substrate and prepared through a one-step solvent-free pyrolysis, the problem of low conversion efficiency and selectivity of existing catalysts is solved. Achieve high-efficiency, low-cost catalytic conversion effect.

CN118698584BActive Publication Date: 2025-01-21WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410742265.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-11
Publication Date
2025-01-21
Estimated Expiration
2044-06-11

AI Technical Summary

Technical Problem

When the existing catalysts convert 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid, the conversion efficiency and selectivity are low, and the preparation method is complex and the cost is high.

Method used

A Co-N-C catalyst is used, which is composed of a three-dimensional multi-level Co nanostructure anchored on a nitrogen-doped carbon material substrate and prepared through a one-step solvent-free pyrolysis to form a catalyst with a high specific surface area and mesoporous structure.

Benefits of technology

Achieving 100% selectivity and 100% conversion rate, efficiently converting 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid, while simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118698584B_ABST
    Figure CN118698584B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of heterogeneous catalysis technology, and in particular to a Co-N-C catalyst for catalytic conversion of 5-hydroxymethylfurfural and a preparation method thereof, wherein the catalyst is composed of a three-dimensional multi-level Co nanostructure anchored on a nitrogen-doped carbon material substrate, wherein the primary nanoparticles composed of Co-N-C are agglomerated into secondary nanoparticles, and the secondary nanoparticles are connected to form a three-dimensional porous coral-like structure. The preparation method of the catalyst includes: S1, mixing hexadecyltrimethylammonium bromide as a structural inducer with cobalt metal salt, zinc metal salt, and 2-methylimidazole; S2, subjecting the mixed powder obtained in step S1 to high-temperature carbonization pyrolysis treatment to obtain a Co-N-C catalyst. The Co-N-C catalyst provided by the present invention has efficient catalytic performance and can catalytically oxidize HMF to 2,5-furandicarboxylic acid with 100% selectivity and 100% conversion rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heterogeneous catalysis, and in particular to a Co-NC catalyst for catalytic conversion of 5-hydroxymethylfurfural and a preparation method thereof. Background Art

[0002] Biomass, as the most abundant and readily available carbon-based renewable energy, is considered a promising fuel and raw material for the production of value-added chemicals. The efficient conversion of renewable raw biomass into high-quality biofuels and important chemicals is an effective way to solve the problems of fossil energy depletion and environmental pollution in today's society. 5-Hydroxymethylfurfural (HMF) extracted from cellulose is recognized as one of the most widely used bio-based platform chemicals. Due to the presence of three functional groups, furan ring, hydroxyl group and aldehyde, HMF can produce a series of high value-added derivatives and fuels through different reaction pathways. Among them, 2,5-furandicarboxylic acid (FDCA) is the most attractive because it has a characteristic structure of dicarboxyl functional groups and can be used as a substitute for petroleum-based terephthalic acid and a precursor for the synthesis of bio-based degradable polyester polyethylene furandicarboxylate (PEF), which is of great significance for environmental protection. In addition, FDCA can also be used in the synthesis of pharmaceuticals, plasticizers, coatings, adhesives and other materials. Therefore, the preparation of FDCA from HMF has received widespread attention and research.

[0003] Precious metal-based catalysts have shown excellent performance in HMF oxidation, but due to the high cost of precious metals and harsh reaction conditions, the development and optimization of non-precious metal-based catalysts remains the main research direction. Transition metal catalysts represented by Co-based materials show catalytic activity far exceeding that of other non-precious metals, among which Co-based catalysts supported by nitrogen-doped carbon materials have the most outstanding advantages. Nitrogen incorporated into the carbon structure can improve the electronic properties of non-precious metal centers by forming active sites by cooperating with metal centers. In addition, it also improves the conductivity of metals or metal oxides, and introduces defects, enhancing catalytic activity. Therefore, Co materials supported by nitrogen-doped carbon materials have been widely studied for the oxidation of HMF.

[0004] Patent CN113198512A provides a nitrogen-carbon doped cobalt-based bimetallic catalyst and a preparation method thereof, comprising the following steps: mixing: mixing a nitrogen source compound, cobalt nitrate, a second metal element nitrate, and a carbon source compound, stirring at 90-120°C for more than 8 hours, filtering and drying to obtain a solid composite containing Co, a second metal element, N, and C elements; calcining: calcining the solid composite under nitrogen conditions to obtain a composite catalyst containing Co, a second metal element, N, and C elements. However, the disadvantage of this technical solution is that the processing operation of the reaction precursor during the preparation of the catalyst is complicated, and long-term stirring is required to remove the solvent, which greatly increases the time cost and the cost of subsequent reaction by-product processing.

[0005] Patent CN115785037A discloses a method for preparing 2,5-furandicarboxylic acid by serially oxidizing 5-hydroxymethylfurfural with a C@CoMn catalyst, wherein HMF, a reaction medium, TBHP and C@CoMn are added to a reaction vessel, stirred for oxidation reaction, and FDCA is obtained; C@CoMn is a catalyst. However, the preparation method of the C@CoMn catalyst is complicated, and the catalyst precursor needs to be prepared by chemical coprecipitation and then calcined. The HMF conversion rate is >99.9%, and the selectivity is 94%, which is lower than the 100% conversion rate and 100% selectivity of the present invention.

[0006] It can be seen that providing a nitrogen-doped carbon material-supported Co material catalyst with a simple, fast and low-cost synthesis method for efficiently and selectively converting HMF to FDCA has broad application prospects and great industrial production potential. Summary of the invention

[0007] In view of this, the present invention proposes a Co-NC catalyst for catalytic conversion of 5-hydroxymethylfurfural and a preparation method thereof, so as to solve the problems of poor conversion efficiency and selectivity of existing catalysts, complex preparation methods and high costs.

[0008] The technical solution of the present invention is achieved in this way:

[0009] In a first aspect, the present invention provides a Co-NC catalyst for catalytic conversion of 5-hydroxymethylfurfural, wherein the catalyst is composed of a three-dimensional multi-level Co nanostructure anchored on a nitrogen-doped carbon material substrate, wherein the primary nanoparticles composed of Co-NC are agglomerated into secondary nanoparticles, and the secondary nanoparticles are connected to form a three-dimensional porous coral-like structure.

[0010] On the basis of the above technical solution, preferably, the diameter of the primary nanoparticles is 20-30 nm, the diameter of the secondary nanoparticles is 200-400 nm, and the catalyst contains a mesoporous structure of 2-10 nm.

[0011] In the present invention, the three-dimensional porous coral-like structure of the catalyst is formed by agglomerating the primary nanoparticles of Co-NC into secondary nanoparticles, and the secondary nanoparticles are connected. The diameter of the primary nanoparticles is 20-30nm, and the diameter of the secondary nanoparticles is 200-400nm. This hierarchical structure can significantly increase the specific surface area of ​​the catalyst, increase the contact area between the reactant and the catalyst, and thus improve the catalytic efficiency. The primary nanoparticles are small in size and large in specific surface area, and can provide more active sites; the secondary nanoparticles are large in size, which is conducive to the diffusion of reactants and products inside the catalyst, promotes material transport, and increases the catalytic reaction rate. The catalyst contains a large number of 2-10nm mesoporous structures, which can accommodate and enrich 5-hydroxymethylfurfural molecules, significantly increase their concentration on the catalyst surface, and also provide channels for the diffusion of 5-hydroxymethylfurfural molecules inside the catalyst, accelerating the reaction. In addition, the mesoporous structure is also conducive to the diffusion and desorption of the reaction product 2,5-furandicarboxylic acid, avoiding the accumulation of products on the catalyst surface and causing catalyst deactivation.

[0012] On the basis of the above technical solution, preferably, the active component of the catalyst is Co nanoparticles, and the content of the Co nanoparticles is 0.2-3.5wt%.

[0013] The content of Co nanoparticles in the catalyst is 0.2-3.5wt%, which can provide sufficient active sites and avoid catalyst deactivation caused by excessive aggregation of Co nanoparticles. The synergistic effect of Co nanoparticles and N and C elements can regulate the electronic structure of Co, improve the reducibility and oxidizability of Co, and thus accelerate the oxidative dehydrogenation reaction of 5-hydroxymethylfurfural and the formation of 2,5-furandicarboxylic acid.

[0014] In a second aspect, the present invention provides a method for preparing a Co-NC catalyst for catalytic conversion of 5-hydroxymethylfurfural, characterized in that it comprises the following steps:

[0015] S1, mixing cetyltrimethylammonium bromide as a structure inducing agent with cobalt metal salt, zinc metal salt and 2-methylimidazole;

[0016] S2. The mixed powder obtained in step S1 is subjected to high-temperature carbonization and pyrolysis treatment to obtain a Co-NC catalyst.

[0017] Specifically, in step S1, 2-methylimidazole is used as a nitrogen source and a carbon source, and a N-doped carbon-based skeleton can be formed during the pyrolysis process, providing the basic structure and N-coordination active sites of the catalyst; cobalt metal salt is used as a Co source, and is reduced to generate Co nanoparticles during the pyrolysis process, which are used as the active component of the catalyst; zinc metal salt is used as an auxiliary agent, and the size and dispersibility of Co nanoparticles can be regulated to prevent Co nanoparticles from agglomerating and growing at high temperatures. On the one hand, hexadecyltrimethylammonium bromide can be used as a structural inducer to induce the connection of secondary nanoparticles to form a three-dimensional porous coral-like structure. Hexadecyltrimethylammonium bromide molecules can electrostatically interact or coordinately bond with catalyst precursors. These forces help promote the aggregation and interconnection between secondary nanoparticles, and finally form a three-dimensional porous coral-like network structure. This unique three-dimensional porous structure can provide abundant mass transfer channels and active sites for reactants, and enhance catalytic performance. On the other hand, during the pyrolysis process, as the temperature increases, hexadecyltrimethylammonium bromide decomposes at high temperature, and the generated gas and carbon residues can form a mesoporous structure inside the catalyst. The mesoporous structure is conducive to the diffusion of reactants and products and improves the catalytic efficiency.

[0018] This preparation method is a solvent-free reaction. Compared with the traditional solvent method, no solvent is added, and the preparation process does not require washing and drying processes. The preparation operation is simpler, more environmentally friendly, and easy to scale up and industrialize.

[0019] On the basis of the above technical solution, preferably, in step S1, the cobalt metal salt is cobalt acetylacetonate, and the zinc metal salt is zinc acetylacetonate.

[0020] On the basis of the above technical scheme, preferably, in step S1, the molar ratio of the 2-methylimidazole, the zinc metal salt and the cobalt metal salt is 4:1:0.01-0.1, and the added mass of the hexadecyltrimethylammonium bromide is 0.01-0.3% of the total mass of the 2-methylimidazole, the zinc metal salt and the cobalt metal salt.

[0021] The ratio of cobalt metal salt to zinc metal salt affects the morphology (specific surface area, etc.) of the catalyst, because Co-Zn-MOFs are formed at a holding temperature of 200°C and then pyrolyzed to form a Co-NC catalyst. During this process, Zn will be evaporated, leaving additional holes and channels in the Co-NC catalyst. Therefore, the introduction and evaporation of zinc helps to create a more porous and interconnected structure, increase the specific surface area of ​​the catalyst and the number of accessible active sites. Hexadecyltrimethylammonium bromide (CTAB) can induce the connection of secondary nanoparticles to form a three-dimensional porous coral-like structure with more mesoporous structures, which is conducive to the diffusion of reactants and products, increases adsorption sites, and improves catalytic efficiency. Excessive CTAB will cause the secondary particles to agglomerate (excessive connection), thereby reducing the active specific surface area and resulting in a decrease in catalytic performance.

[0022] On the basis of the above technical scheme, preferably, in step S2, the process conditions of the pyrolysis treatment are: under inert atmosphere conditions, starting from 20-30°C, heating at a heating rate of 1-5°C / min to 200-300°C, keeping warm for 1-2h, then heating to 800-1000°C at a heating rate of 5-10°C / min, and keeping warm for 2-3h.

[0023] When the pyrolysis process is kept at 200-300℃, a Co-Zn metal organic framework will be formed. The Co-Zn metal organic framework material (MOFs) has a porous structure; when the temperature is continued to rise to 800-1000℃, the Co-Zn-MOFs material will carbonize to form a N-doped carbon-based skeleton (NC). At high temperatures, 2-methylimidazole decomposes and reacts with the MOFs skeleton to form a stable NC structure. At the same time, due to the low boiling point of Zn (907℃), part of the Zn will evaporate at high temperatures, leaving additional holes and channels in the NC skeleton to form a Co-NC catalyst.

[0024] On the basis of the above technical solution, preferably, in step S2, the inert gas is argon or nitrogen, and the gas flow rate is 50-100 cc / min.

[0025] In a third aspect, the present invention provides an application of a Co-NC catalyst, wherein the catalyst is used for a reaction of converting 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid.

[0026] On the basis of the above technical solution, preferably, the catalytic environment of the catalyst is weakly alkaline and water solvent conditions.

[0027] The use of Co-NC catalyst to convert HMF into FDCA under weak alkaline and water solvent conditions can improve the stability of HMF, promote the oxidation reaction, increase the solubility of FDCA, maintain the stability of the catalyst, and conform to the concept of green chemistry, with good technical and economic feasibility.

[0028] The Co-NC catalyst for catalytic conversion of 5-hydroxymethylfurfural and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0029] (1) The Co-NC catalyst involved in the present invention has a unique structure. Microscopically, it is composed of primary nanoparticles of Co-NC (diameter of about 20-30nm) agglomerated into secondary nanoparticles (diameter of about 200-400nm), and the secondary particles are connected to form a three-dimensional porous coral-like structure; the active component is Co nanoparticles, wherein the content of Co is 0.2-3.5wt%, and has abundant catalytic active sites; at the same time, the catalyst has a large number of 2-10nm mesoporous structures, which are conducive to the diffusion of reactants and products and increase adsorption sites. The above characteristics make the catalyst have efficient catalytic performance. Experimental results show that the Co-NC catalyst can catalytically oxidize HMF to FDCA with 100% selectivity and 100% conversion rate;

[0030] (2) The Co-NC catalyst involved in the present invention is prepared by a one-step solvent-free pyrolysis method. The morphology structure and specific surface area of ​​the catalyst can be effectively controlled by changing the ratio of metal salts and the amount of cetyltrimethylammonium bromide added. The structure and performance of the catalyst are highly controllable. At the same time, cetyltrimethylammonium bromide can be used as a structure inducer to induce the secondary nanoparticles to connect to form a three-dimensional porous coral-like structure, so that the Co-NC catalyst of the present invention presents a special three-dimensional porous coral-like structure.

[0031] (3) The Co-NC catalyst involved in the present invention can prepare the target product by one-step pyrolysis. The one-step synthesis reduces the required steps and the intermediate processing process. The preparation process is simple and thus greatly reduces the preparation cost. At the same time, the preparation process is solvent-free, and the target product can be used for catalytic reaction without subsequent treatment, which is green and environmentally friendly. Therefore, the one-step solvent-free large-scale preparation of Co-NC catalysts of the present invention has good industrial production potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 This is the XRD pattern of the Co-NC catalyst prepared in Example 1 of the present invention;

[0034] Figure 2 This is a SEM image of the Co-NC catalyst prepared in Example 1 of the present invention;

[0035] Figure 3TEM image of the Co-NC catalyst prepared in Example 1 of the present invention;

[0036] Figure 4 This is a sample picture of the Co-NC catalyst obtained in Example 1 of the present invention;

[0037] Figure 5 This is a nitrogen adsorption-desorption curve diagram of the Co-NC catalyst prepared in Examples 1-6 of the present invention;

[0038] Figure 6 This is a pore size distribution diagram of the Co-NC catalyst prepared in Examples 1-6 of the present invention;

[0039] Figure 7 XRD diagram of the Co-NC catalyst prepared in Examples 1-6 of the present invention;

[0040] Figure 8 The Raman graph of the Co-NC catalyst prepared in Examples 1-6 of the present invention;

[0041] Fig. 9 This is a SEM comparison picture of the Co-NC catalysts prepared in Examples 2, 5-6 of the present invention. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] This embodiment provides a Co-NC catalyst and a preparation method thereof, and the specific steps are as follows:

[0045] S1, respectively taking 40mmol 2-methylimidazole, 10mmol zinc acetylacetonate, 1mmol cobalt acetylacetonate and 10mg CTAB, putting them in a mortar and grinding them for 10min into a fine powder with uniform color to obtain material A1;

[0046] S2, evenly spread the material A1 obtained in step S1 in a porcelain boat, then place the porcelain boat in a tube furnace, introduce argon gas for heating treatment, the gas flow rate is 50cc / min, heat up to 200°C at a heating rate of 4°C / min at room temperature, keep warm for 1h, then heat up to 920°C at a heating rate of 5°C / min, keep warm for 2h, and cool to room temperature with the furnace after heating to obtain a Co-NC catalyst;

[0047] The prepared Co-NC catalyst was further used as a catalyst for the conversion of HMF to FDCA as follows:

[0048] S3, weigh 30 mg of the catalyst Co-NC-1 obtained in step S2, 0.25 mmol of HMF and 0.75 mmol of potassium bicarbonate (KHCO 3、 Place in a reaction tube, add 2 ml of deionized water, place the reaction tube on a magnetic heating stirrer, and react at 90° C. for 12 hours.

[0049] After testing, the yield of FDCA obtained in this example was 100%. After condition optimization, under the same test conditions as in step S3 above, 0.5 mmol of KHCO3 was added and the reaction time was 9 hours, the yield of FDCA obtained was still 100%.

[0050] Example 2

[0051] This embodiment provides a Co-NC catalyst and a preparation method thereof, and the specific steps are as follows:

[0052] S1, respectively taking 40mmol 2-methylimidazole, 10mmol zinc acetylacetonate, 0.1mmol cobalt acetylacetonate and 10mg CTAB, putting them in a mortar and grinding them for 10min into a fine powder with uniform color, to obtain material A2;

[0053] S2, evenly spread the material A2 obtained in step S1 in a porcelain boat, then place the porcelain boat in a tube furnace, introduce argon gas for heating treatment, the gas flow rate is 50cc / min, heat up to 200°C at a heating rate of 4°C / min at room temperature, keep warm for 1h, then heat up to 920°C at a heating rate of 5°C / min, keep warm for 2h, and cool to room temperature with the furnace after heating to obtain a Co-NC catalyst;

[0054] The prepared Co-NC catalyst was further used as a catalyst for the conversion of HMF to FDCA as follows:

[0055] S3. Weigh 30 mg of the Co-NC catalyst obtained in step S2, 0.25 mmol of HMF and 0.75 mmol of potassium bicarbonate (KHCO3), respectively, and place them in a reaction tube. Add 2 ml of deionized water thereto. Place the reaction tube on a magnetic heating stirrer and react at 90° C. for 12 hours.

[0056] After testing, the yield of FDCA obtained in this example is 79%.

[0057] Example 3

[0058] This embodiment provides a Co-NC catalyst and a preparation method thereof, and the specific steps are as follows:

[0059] S1, respectively taking 40mmol 2-methylimidazole, 10mmol zinc acetylacetonate, 0.2mmol cobalt acetylacetonate and 10mg CTAB, putting them in a mortar and grinding them for 10min into a fine powder with uniform color, to obtain material A3;

[0060] S2, evenly spread the material A3 obtained in step S1 in a porcelain boat, then place the porcelain boat in a tube furnace, introduce argon gas for heating treatment, the gas flow rate is 50cc / min, heat up to 200°C at a heating rate of 4°C / min at room temperature, keep warm for 1h, then heat up to 920°C at a heating rate of 5°C / min, keep warm for 2h, and cool to room temperature with the furnace after heating to obtain a Co-NC catalyst;

[0061] The prepared Co-NC catalyst was further used as a catalyst for the conversion of HMF to FDCA as follows:

[0062] S3. Weigh 30 mg of the Co-NC catalyst obtained in step S2, 0.25 mmol of HMF and 0.75 mmol of potassium bicarbonate (KHCO3), respectively, and place them in a reaction tube. Add 2 ml of deionized water thereto. Place the reaction tube on a magnetic heating stirrer and react at 90° C. for 12 hours.

[0063] After testing, the yield of FDCA obtained in this example is 54%.

[0064] Example 4

[0065] This embodiment provides a Co-NC catalyst and a preparation method thereof, and the specific steps are as follows:

[0066] S1, respectively taking 40 mmol 2-methylimidazole, 10 mmol zinc acetylacetonate, 0.3 mmol cobalt acetylacetonate and 10 mg CTAB, putting them in a mortar and grinding them for 10 min into a fine powder with uniform color, to obtain material A4;

[0067] S2, evenly spread the material A4 obtained in step S1 in a porcelain boat, then place the porcelain boat in a tube furnace, introduce argon gas for heating treatment, the gas flow rate is 50cc / min, heat up to 200°C at a heating rate of 4°C / min at room temperature, keep warm for 1h, then heat up to 920°C at a heating rate of 5°C / min, keep warm for 2h, and cool to room temperature with the furnace after heating to obtain a Co-NC catalyst;

[0068] The prepared Co-NC catalyst was further used as a catalyst for the conversion of HMF to FDCA as follows:

[0069] S3. Weigh 30 mg of the Co-NC catalyst obtained in step S2, 0.25 mmol of HMF and 0.75 mmol of potassium bicarbonate (KHCO3), respectively, and place them in a reaction tube. Add 2 ml of deionized water thereto. Place the reaction tube on a magnetic heating stirrer and react at 90° C. for 12 hours.

[0070] After testing, the yield of FDCA obtained in this example is 25%.

[0071] Example 5

[0072] This embodiment provides a Co-NC catalyst and a preparation method thereof, and the specific steps are as follows:

[0073] S1, respectively taking 40mmol 2-methylimidazole, 10mmol zinc acetylacetonate, and 0.1mmol cobalt acetylacetonate, put them in a mortar and grind them for 10min into fine powder with uniform color to obtain material A5;

[0074] S2, evenly spread the material A5 obtained in step S1 in a porcelain boat, then place the porcelain boat in a tube furnace, introduce argon gas for heating treatment, the gas flow rate is 50cc / min, heat up to 200°C at a heating rate of 4°C / min at room temperature, keep warm for 1h, then heat up to 800°C at a heating rate of 5°C / min, keep warm for 2h, and cool to room temperature with the furnace after heating to obtain a Co-NC catalyst;

[0075] The prepared Co-NC catalyst was further used as a catalyst for the conversion of HMF to FDCA as follows:

[0076] S3. Weigh 30 mg of the Co-NC catalyst obtained in step S2, 0.25 mmol of HMF and 0.75 mmol of potassium bicarbonate (KHCO3), respectively, and place them in a reaction tube. Add 2 ml of deionized water thereto. Place the reaction tube on a magnetic heating stirrer and react at 90° C. for 16 hours.

[0077] After testing, the yield of FDCA obtained in this example is 45%.

[0078] Example 6

[0079] This embodiment provides a Co-NC catalyst and a preparation method thereof, and the specific steps are as follows:

[0080] S1, respectively taking 40 mmol 2-methylimidazole, 10 mmol zinc acetylacetonate, 0.1 mmol cobalt acetylacetonate and 20 mg CTAB, putting them in a mortar and grinding them for 10 min into a fine powder with uniform color, to obtain material A6;

[0081] S2, evenly spread the material A6 obtained in step S1 in a porcelain boat, then place the porcelain boat in a tube furnace, introduce argon gas for heating treatment, the gas flow rate is 100cc / min, heat up to 300°C at a heating rate of 4°C / min at room temperature, keep warm for 1h, then heat up to 1000°C at a heating rate of 5°C / min, keep warm for 3h, and after heating, cool to room temperature with the furnace to obtain a Co-NC catalyst;

[0082] The prepared Co-NC catalyst was further used as a catalyst for the conversion of HMF to FDCA as follows:

[0083] S3. Weigh 30 mg of the Co-NC catalyst obtained in step S2, 0.25 mmol of HMF and 0.75 mmol of potassium bicarbonate (KHCO3), respectively, and place them in a reaction tube. Add 2 ml of deionized water thereto. Place the reaction tube on a magnetic heating stirrer and react at 90° C. for 16 hours.

[0084] After testing, the yield of FDCA obtained in this example is 50%.

[0085] Comparative Example 1

[0086] This comparative example is basically the same as Example 1, except that KHCO3 is no longer added to the catalytic reaction in step S3: 30 mg of the catalyst Co-NC-1 obtained in step S2 and 0.25 mmol of HMF are weighed respectively and placed in a reaction tube, 2 ml of deionized water is measured and added thereto, the reaction tube is placed on a magnetic heating stirrer, and the reaction is carried out at 90°C for 12 hours.

[0087] After testing, the yield of FDCA obtained in this example is 1%.

[0088] Comparative Example 2

[0089] This comparative example is basically the same as Example 1, except that no catalyst is added to the catalytic reaction in step S3: 0.25 mmol of HMF and 0.75 mmol of potassium bicarbonate are weighed and placed in a reaction tube, 2 ml of deionized water is measured and added thereto, and the reaction tube is placed on a magnetic heating stirrer and reacted at 90° C. for 12 hours.

[0090] After testing, the yield of FDCA obtained in this example was 0%.

[0091] Performance Testing

[0092] The Co content in the catalysts prepared in Examples 1-6 was tested, and the catalytic activity of the catalysts was tested. The test results are shown in Table 1.

[0093] Table 1

[0094] Sample Cocontent (wt%) Example 1 3.50 Example 2 0.36 Example 3 0.25 Example 4 0.65 Example 5 0.31 Example 6 0.38

[0095] Figure 1 This is the XRD pattern of the Co-NC catalyst prepared in Example 1. The characteristic peaks corresponding to the three crystal planes (111), (220) and (200) of Co and the characteristic peak corresponding to the C (002) crystal plane can be clearly observed, indicating that Co exists in the form of nanoparticles in the Co-NC catalyst.

[0096] Figure 2 This is a SEM image of the Co-NC catalyst prepared in Example 1, showing that the primary nanoparticles (diameter of about 30-50 nm) of Co-NC are agglomerated into secondary nanoparticles (diameter of about 400-500 nm), and the secondary particles are connected to form a three-dimensional porous coral-like structure.

[0097] Figure 3 This is a TEM image of the Co-NC catalyst prepared in Example 1, which shows that Co nanoparticles (interplanar spacing 0.208 nm, corresponding to Co (111) crystal plane) are uniformly distributed in the nitrogen-carbon material, which is consistent with the above characterization test results. Figure 4 This is a gram-scale sample preparation diagram of the Co-NC catalyst prepared in Example 1.

[0098] Figure 5 is a nitrogen adsorption-desorption curve diagram of the Co-NC catalyst prepared in Example 1-6, Figure 6 The pore size distribution diagram of the Co-NC catalysts prepared in Examples 1-6. Combining the two figures, it can be seen that the Co-NC catalyst prepared in Example 1 has a more mesoporous structure, which is more conducive to the transmission of reactants and products than the catalysts prepared in other examples, and has more adsorption sites, thereby making the catalytic performance of the material more outstanding.

[0099] Figure 7 This is the XRD pattern of the Co-NC catalyst prepared in Example 1-6. Figure 8 The Raman graphs of the Co-NC catalysts prepared in Examples 1-6 show that the Co-NC catalyst prepared in Example 1 has a high degree of graphitization, which is beneficial to the electron transport process during the catalytic reaction and improves the catalytic activity.

[0100] Fig. 9 The SEM images of the Co-NC catalysts prepared in Example 2, Example 5 and Example 6 show that hexadecyltrimethylammonium bromide (CTAB) as a structural inducer can induce the connection of secondary nanoparticles to form a three-dimensional porous coral-like structure. Excessive CTAB (Example 6) will cause the secondary particles to agglomerate (excessive connection), thereby reducing the active specific surface area and resulting in a decrease in catalytic performance.

[0101] By comparing Example 1 and Comparative Example 1, it can be seen that the Co-NC catalyst can hardly catalyze the oxidation of HMF to obtain FDCA under non-alkaline conditions, indicating that the catalyst has poor oxidizability under non-alkaline conditions.

[0102] By comparing Example 1 and Comparative Example 2, it can be seen that, in the absence of a catalyst, in the environment of weak alkalinity and water solvent, HMF cannot be spontaneously oxidized to obtain FDCA, which proves the catalytic effect of the catalyst.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A Co-NC catalyst for catalytic conversion of 5-hydroxymethylfurfural, characterized in that: The catalyst is composed of a three-dimensional multi-level Co nanostructure anchored on a nitrogen-doped carbon material substrate, in which primary nanoparticles composed of Co-NC are agglomerated into secondary nanoparticles, and the secondary nanoparticles are connected to form a three-dimensional porous coral-like structure; The diameter of the primary nanoparticles is 20-30 nm, the diameter of the secondary nanoparticles is 200-400 nm, and the catalyst contains a mesoporous structure of 2-10 nm; The active component of the catalyst is Co nanoparticles, and the content of the Co nanoparticles is 0.2-3.5wt%; The preparation method of the catalyst comprises the following steps: S1, mixing cetyltrimethylammonium bromide as a structure inducing agent with cobalt metal salt, zinc metal salt and 2-methylimidazole; S2, subjecting the mixed powder obtained in step S1 to high-temperature carbonization pyrolysis treatment under an inert atmosphere to obtain a Co-NC catalyst; In step S1, the cobalt metal salt is cobalt acetylacetonate, and the zinc metal salt is zinc acetylacetonate.

2. A Co-NC catalyst for catalytic conversion of 5-hydroxymethylfurfural according to claim 1, characterized in that: In step S1, the molar ratio of the 2-methylimidazole, the zinc metal salt and the cobalt metal salt is 4:1:0.01-0.1, and the added mass of the hexadecyltrimethylammonium bromide is 0.01-0.3% of the total mass of the 2-methylimidazole, the zinc metal salt and the cobalt metal salt.

3. A Co-NC catalyst for catalytic conversion of 5-hydroxymethylfurfural according to claim 1, characterized in that: In step S2, the process conditions of high-temperature carbonization pyrolysis treatment are: under inert atmosphere conditions, starting from 20-30°C, heating at a heating rate of 1-5°C / min to 200-300°C, keeping warm for 1-2h, and then heating to 800-1000°C at a heating rate of 5-10°C / min, keeping warm for 2-3h.

4. A Co-NC catalyst for catalytic conversion of 5-hydroxymethylfurfural as claimed in claim 3, characterized in that: In step S2, the inert gas is argon or nitrogen, and the gas flow rate is 50-100 cc / min.

5. The use of a Co-NC catalyst for catalytic conversion of 5-hydroxymethylfurfural according to any one of claims 1 to 4, characterized in that: The catalyst is used to convert 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid.

6. The use of a Co-NC catalyst for catalytic conversion of 5-hydroxymethylfurfural as claimed in claim 5, characterized in that: The catalytic environment of the catalyst is weakly alkaline and water solvent conditions.

Citation Information

Patent Citations

  • Nitrogen-carbon doped cobalt-based bimetallic catalyst, preparation method thereof and preparation method of 2, 5-dimethyl furandicarboxylate

    CN113198512A

  • Catalyst for converting 5-hydroxymethylfurfural into 2, 5-furandicarboxylic acid and preparation method thereof

    CN116870948A